Analysis of CT imaging changes of psoas major muscles in patients with lumbar disc herniation mainly based on low back pain and lower limb pain - Cui, Mingchao; Zhang, Qianru; Chen, Xipeng; Wu, Han (Frontiers in Surgery, 2023)
Background: The study aimed to compare the area changes of CT (computed tomograghy) imaging of psoas major muscle (PM) in patients with lumbar disc herniation (LDH) mainly based on low back pain (LBP) and lower limb pain (LLP), and to analyze the correlation among them. Methods: We retrospectively analyzed the lumbar CT imaging data of 120 patients with LDH and 60 healthy control people in our hospital from July 2017 to August 2019. They were divided into LBP group (60 cases), LLP group (60 cases) and healthy controls group (60 cases). According to the pain duration and pain degree, LBP group and LLP group were divided into three subgroups respectively. The maximum cross-sectional area (CSA) of PM and the CSA of L5 vertebral body were calculated by Image J software, and the ratio of them was the maximum CSA index of PM. The maximum CSA indices of PM among three groups and three subgroups were compared, respectively. Results: The baseline data among the three groups weren’t significantly different (P > 0.05), yet the maximum CSA index of PM did (P < 0.05). In the LBP group, the maximum CSA indices of PM among the three subgroups (short, medium and long) according to the pain duration were significantly different (P < 0.05), and those among the three subgroups (light, medium and heavy) according to pain degree did (P < 0.05). In the LLP group, the maximum CSA indices of PM among the three subgroups (short, medium and long) were compared, but there was not statistical difference among the three subgroups (P > 0.05). No statistical difference in terms of the maximum CSA indices of PM among the three subgroups (light, medium and heavy) was observed (P > 0.05). Conclusions: The atrophy and thinning of PM may be related to LDH. The correlation between the atrophy of PM and LBP was greater than that of LLP. The atrophy of PM in LDH patients with LBP increased with the prolongation of pain duration and aggravation of pain degree.